A study of social resistance, religious radicalism and thought of dayah scholars - Risna Dewi, Fajri M Kasim, Kamaruddin M Said, Fauzi Abdurrahman,; Muhammad, Zikri; Rizwan, M. (Opción, 2019)
This article describes public resistance to religious radical groups and the relationship between the religious thought of Dayah scholars ulama with moderate Islam (Rahamata lil alamin) in Aceh Indonesia via comparative qualitative research methods. As a result, the need for understanding wasathiyyah is found to be significant in today’s increasingly plural society. In conclusion, from sociological aspects, moderate Islam preached by Dayah scholars in Aceh help to reduce the potential of social conflicts in the community.